2020
DOI: 10.1038/s42004-020-00340-x
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus zwitterions engaged in a conjugated macrocycle on fullerene

Abstract: Organophosphorus zwitterions are one of the most important but elusive intermediates for carbon-carbon bond formation in synthetic chemistry and biology. However, a lack of isolated examples due to their lability has hampered in-depth understanding of structures and their reaction mechanisms. In this study, we crystallographically reveal the solid-state structure of a phosha-Michael adduct engaged in a cage-opened C 60 skeleton, which is formed as a kinetic product. This compound exhibits dark brown colour in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…The structure of the phosphorus ylid, HF@ 4 , was suggested by close agreement of a calculated 13 C NMR spectrum of 4 with the experimental spectrum of the regioisomer shown in Scheme 1, [19a] and we have now confirmed the structure of 4 by X‐ray crystallography (Figure 2). The crystal structure reveals that the C=O bond (1.223 Å) of the carbonyl group adjacent to the phosphorus ylid moiety is longer than those of the remote carbonyl groups (1.209 Å and 1.202 Å), suggesting that the ylid has substantial enolate character which may explain its good stability [21] …”
Section: Resultsmentioning
confidence: 98%
“…The structure of the phosphorus ylid, HF@ 4 , was suggested by close agreement of a calculated 13 C NMR spectrum of 4 with the experimental spectrum of the regioisomer shown in Scheme 1, [19a] and we have now confirmed the structure of 4 by X‐ray crystallography (Figure 2). The crystal structure reveals that the C=O bond (1.223 Å) of the carbonyl group adjacent to the phosphorus ylid moiety is longer than those of the remote carbonyl groups (1.209 Å and 1.202 Å), suggesting that the ylid has substantial enolate character which may explain its good stability [21] …”
Section: Resultsmentioning
confidence: 98%
“…Recently, we reported zwitterionic cage‐opened C 60 derivatives bearing a phosphonium substituent, that is, 1‐phosphonium‐5‐oxabetaine and β‐oxo‐phosphorus ylide by the reaction with phosphines PR 3 (Figure 1). [15] In the latter case, the Kukhtin‐Ramirez adduct was found to play an indispensable role. We now moved our focus to reactions of phosphites P(OR) 3 with a conjugate macrocyclic orifice on cage‐opened C 60 derivatives [16] .…”
Section: Figurementioning
confidence: 98%
“…The results on addition of P(OMe) 3 to the C(2)=O(2) and C(3)=O(3) groups were summarized in Table 1 and Figures S51,52. In all cases, nucleophilic attack to the oxygen atom ( TS‐O ) is unfavorable since activation barriers are estimated to be over 32 kcal mol −1 which is nearly 5 kcal mol −1 higher than those for PR 3 , [15] likely due to the lower nucleophilicity of P(OR) 3 [23] . Thus, the nucleophilic addition of P(OMe) 3 initially takes place at the carbonyl carbon atom in SM via TS‐C which provides classical Abramov intermediate, that is, INT‐C bearing a P−C bond.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…11c Recently, we found that b-oxo-phosphorus ylide INT2a 0 bearing a PR 3 unit with a cone angle smaller than 140 is signicantly hydrolysed in the presence of water. 17 As to the conversion from INT3a 0 to 3a 0 , P(OiPr) 3 was previously found to exhibit high performance. 18 For the efficient synthesis of H 2 O@C 60 , we designed one-pot reaction from 2f to H 2 O@3f via three steps commenced with the H 2 O-insertion under high-pressure conditions followed by stepwise conversion of the thus formed H 2 O@2f into H 2 O@INT3f and then H 2 O@3f.…”
mentioning
confidence: 99%